The world of squirrels - Coldrey, Jennifer; Oxford Scientific Films (Milwaukee : Gareth Stevens Pub., 1986)
Describes, in simple text and photographs, the lives of squirrels in their natural habitat explaining how they feed, defend themselves, and breed.
Includes index.
Keywords: Squirrels -- Juvenile literature; Squirrels